Модели формирования института венчурных инвестиций - Иван Иванович Родионов; Николай Николаевич Дмитриев (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
The purpose of this article is to highlight most critical issues related to Russian venture business. It provides a broad analysis of the modell of state support of creation of the venture financing institute in Russia, with particular reference to incentives required promote venture financing, and the role of venture market participants. It sets out a number of governmental measures aimed at establishing venture capital funds on the basis of public/private partnership